Economics through graphs - Singh, Manoj (ed.); Singh, Sanjeev K (ed.); Singh, Meenakshi (ed.) (New Delhi DPS Publishing House, 2020)
Economic Theory is very rich in graphs. This special Compilation convinced in the belief that we do not know as much as we should about the importance of visual interpretation in development of economic theory as well as it's interpretation among various courses of human life governance. The book has aim to provide account of role of each of the chosen graphs in economic analysis, taking it's theoretical background and explanations into consideration. Widely speaking graphs are now part of modem toolbox for economist, social scientists, policy makers, executives and students. In book we have selected graphs that have been influential, prominent and particle in the history of economic theory as well as it's application to socio political administrative life of mankind.
Keywords: IAS as an editor; Economics